Alternative medicine: a critical view of homeopathy - Álvarez Ramírez, Lorenzo (Spei Domus, 2022)
Homeopathy is one of the most widely used practices in alternative medicine, both in the care of human patients and in veterinary medicine. Its origin dates back a little over 200 years and its popularity has been up and down ever since. Since its beginning and until modern times, the postulates of homeopathy have been the subject of debates in medicine and science. Concepts applied in homeopathy such as similia similibus curentur, vital force, dynamization, minimum or infinitesimal doses, and other peculiarities of the practice, are currently little recognized or even completely rejected. The weakness of homeopathy's theoretical framework and the scant of serious evidence it has provided makes it difficult to consider it as a tool of modern scientific medicine. In this review of the available literature, the principles of homeopathy, the experimental evidence of its efficacy, and its suitability in current medicine are described in a critical and rigorous way, to determine whether it can be considered an acceptable medical and veterinary practice in the XXI century.
Keywords: alternative medicine; homeopathy; complementary medicine; scientific medicine